Experiências, memórias e subjetividades femininas em As meninas, de Lygia Fagundes Telles, e a Veinte años, Luz, de Elsa Osorio - Cargnelutti, Camila Marchesan (2023)
This research proposes a study about the possible forms of construction of other versions of Latin American dictatorships from the literature of subjects historically considered as otherness in patriarchal contexts. The study analyzes novels by female authorship from two Latin American countries (Brazil and Argentina), investigating the experiences of female characters, with the aim of making their stories emerge in doubly oppressive contexts – for their political ideologies and for their gender. The main objective is to make a comparative literary analysis between two Latin American novels published in dictatorial or post-dictatorial contexts. The main objective is to understand how other versions of the history of dictatorships in these two countries are constructed and what are the experiences of women manifested in these works, based on the emergence of gender perspectives – the analytical category of difference used here – in the literary dimension of two Latin American novels. In the Brazilian context, the study includes the analysis of As meninas, by Lygia Fagundes Telles, published in 1973. In Argentina, includes the novel A veinte años, Luz, by Elsa Osorio, published in 1998. To reach the objectives, the investigation covers, at first, a bibliographic review about feminist theory and criticism, gender, female authorship, literature, history and memory, considering the interdisciplinary nature of the theme. In addition, this study seeks to understand the narratives historical and literary context to achieve greater analytical complexity about the time and the themes. The novels analysis is constructed under a comparative bias and with conceptual tools of feminist theory and criticism. Articulating the literary with historical, cultural and social elements, the analysis of As meninas and A veinte años, Luz explores the manifestation of these elements and the experiences of the female characters in the fictional universe of the works. The final considerations contain a comparison, identifying singularities and establishing similarities between the novels. Among these, are highlighted the complex interrelationships between literature and history, the representation of female characters, the different transformations of the patriarchal oppression system, the political and gender violence duplicity, the female narrative perspectives, the spatial and temporal dimensions and the discussions about individual and collective memory